La cultura del cuerpo en el Islam - Alshboul, Ayman (Nómadas. Critical Journal of Social and Juridical Science, 2012)
This Study analyzes four fundamental aspects that are directly related to the body in Islam. The first focuses on the deep relationship between the body and religion, the second analyzes the religious rituals that human beings must make in way of thanking God. The third aspect of this work emphasizes the close relationship between body and soul, the body as profane material and the soul as spiritual and eternal, because each depends on the other, the body is still alive without the soul and vice versa, and the sett appearance highlighted the importance of the mind to the body.In conclusion the body is not the only set of living organs; it is also a social carrier of encodings. Hence, from a religious perspective, the body can be understood as religious variable correlated with multiple meanings to the acts and liturgical practices of the religion. It also acquires its meaning through adscription and projections in social and cultural contexts.
Keywords: Islam; Body; Spirit; Soul; Mind; birth; Death; Circumcision